EDUTAINMENT GAMES FOR ISLAMIC AND SDGS-ORIENTED ENGLISH LEARNING: A CRITICAL LITERATURE REVIEW ON WRITING DEVELOPMENT AND GRAMMAR MASTERY - Kalayo Hasibuan; Sutarmo; Harum Natasha; Chandra Alfindodes (English Study Program University of Pasir Pengaraian, 2026)
The increasing demand for engaging, contextualized, and values-oriented English language teaching has strengthened scholarly interest in edutainment games in EFL contexts. Beyond functioning as motivational tools, educational games are increasingly viewed as pedagogical mediators that support linguistic development, character education, and sustainability awareness. However, research on game-based grammar and writing instruction, Islamic values integration, and Sustainable Development Goals (SDGs)-oriented learning has largely been conducted separately. This critical literature review examines how edutainment games support writing development and grammar mastery in EFL learning while integrating Islamic values and SDGs themes. Using a narrative critical review with thematic synthesis, the study analyzes scholarship published between 2021 and 2026 from Scopus, Web of Science, ERIC, and Google Scholar. The findings indicate that edutainment games improve learner motivation, grammatical accuracy, vocabulary retention, contextual language use, collaboration, and higher-order thinking. When combined with Islamic and SDGs-oriented themes, games may also promote ethical awareness, character formation, ecological consciousness, and sustainability literacy. Unlike previous reviews that mainly focus on gamification for engagement, this review proposes a tripartite conceptual framework positioning edutainment game as vehicles for simultaneous linguistic development, moral formation, and sustainability-oriented learning. The article contributes an emerging research agenda for AI-supported grammar games, serious games for values education, and integrated materials development for Global South contexts. The review concludes that the integration of edutainment, Islamic values, and SDGs themes represents a promising but still underdeveloped area in EFL scholarship that requires stronger empirical investigation.